BODIPY-based colorimetric/ratiometric fluorescence probes for sulfite in aqueous solution and in living cells. Issue 111 (27th October 2015) - Liu, Shanshan; Song, Lun; Sun, Qian; Chen, Zhaoyang; Ge, Yu; Zhang, Weibing; Qian, Junhong
Abstract : Two colorimetric/ratiomrtric fluorescence probes for sulfite utilizing the Michael-addition mechanism were designed.BSP1 could be applied in the imaging of sulfite in living cells. Abstract : Two colorimetric/ratiometric fluorescence probes (BSP1 andBSP2 ) for sulfite utilizing the Michael-addition mechanism were designed and synthesized by incorporating a substituted pyridinium/methyl pyridinium to a BODIPY fluorophore linked with an α, β-unsaturated ketone.BSP1 exhibited colorimetric and ratiometric fluorescence responses toward sulfite in PBS-CTAB system. The addition of sulfite to the CC group inBSP1 induced about 60 nm hypsochromic shift in both absorption (from 554 nm to 494 nm) and emission (from 618 nm to 554 nm) spectra accompanied with fluorescent color change from red to green under hand-lamp excited at 365 nm. Good linear relationship was found between the emission ratio ( I 554 / I 618 ) and the concentration of sulfite in the range of 0–300 μM with a detection limit of 6.4 μM. In the case ofBSP2, the probe showed excellent water solubility and faster spectral response to sulfite with about 100 nm blue shift (from 567 nm to 470 nm) in the absorption spectrum in PBS. The solution's color changed from purple to yellow. BothBSP1 andBSP2 displayed high selectivity and competition towards sulfite over other relative species such as thiols and sulfide. More importantly, we have demonstrated thatBSP1 could be applied in the imaging of sulfite in living cells.